Assessing Innovation Performance through Ex-Ante and Ex-Post Patent-Based Measures - Francesca MICHELINO; Antonello CAMMARANO; Mauro CAPUTO (Communications of International Proceedings, 2020)
The paper analyzes the relationships between ex-ante and ex-post measures for innovation performance based on patent data. Results provide suggestions for innovation managers on the leverages to be operated during the innovation process for obtaining high valuable patented technologies.
Keywords: innovation performance; patent data.